Women’s leadership and implications for climate resilience: A conceptual framework - Bryan, Elizabeth; Elias, Marlène; Kosec, Katrina; Kyle, Jordan; Morgan, Miranda; Najjar, Dina (CGIAR System Organization, 2023)
Women are underrepresented in leadership and have more limited influence than men over decisions in climate change governance processes at multiple scales. The CGIAR Initiative on Gender Equality (HER+) has explored public and private sector approaches to increase women’s agency and leadership in agrifood system governance with the goal of increasing women’s climate resilience. However, further research is required to fully explore the mechanisms through which women’s leadership influences climate resilience. This project note develops a conceptual framework that draws on key concepts from the literature on climate change and resilience, and the role of women’s representation in policy processes to trace the pathways through which women’s leadership can support climate resilience. This framework provides insights into key relationships that are deserving of additional focus in the next phase of research.